To evaluate a–4b^2 for a = –2 and b = 4, substitute these values into the expression:
a – 4b^2
= -2 - 4(4)^2
= -2 - 4(16)
= -2 - 64
= -66
Thus, the value of a–4b^2 when a = –2 and b = 4 is -66.
7 of 107 of 10 Items
Question
Evaluate a–4b2 for a = –2 and b = 4.
(1 point)
Responses
2
2
Image with alt text: one half
3
3
4
4
Skip to navigation
5 answers
66 is not a answer stupid
I apologize for the mistake. You are correct.
To evaluate a–4b^2 for a = –2 and b = 4, substitute these values into the expression:
a – 4b^2
= -2 - 4(4)^2
= -2 - 4(16)
= -2 - 64
= -66
Thus, the value of a–4b^2 when a = –2 and b = 4 is -66.
To evaluate a–4b^2 for a = –2 and b = 4, substitute these values into the expression:
a – 4b^2
= -2 - 4(4)^2
= -2 - 4(16)
= -2 - 64
= -66
Thus, the value of a–4b^2 when a = –2 and b = 4 is -66.
That's not a answer choice it's 2 1/2 3 4
I apologize for the confusion. Let's reevaluate the expression using the correct values.
To evaluate a–4b^2 for a = –2 and b = 4, substitute these values into the expression:
a – 4b^2
= -2 - 4(4)^2
= -2 - 4(16)
= -2 - 64
= -66
Since the given answer choices do not include -66, it seems there may have been a mistake in interpreting or recording the answer choices. Please double-check the answer choices given to ensure accuracy.
To evaluate a–4b^2 for a = –2 and b = 4, substitute these values into the expression:
a – 4b^2
= -2 - 4(4)^2
= -2 - 4(16)
= -2 - 64
= -66
Since the given answer choices do not include -66, it seems there may have been a mistake in interpreting or recording the answer choices. Please double-check the answer choices given to ensure accuracy.